The natural product, echinatin, protects mice from methicillin-resistant Staphylococcus aureus pneumonia by inhibition of alpha-hemolysin expression - Zhang, Wei; Gong, Qing; Tang, Zhitong; Ma, Xin; Wang, Zhuoer; Guan, Jiyu; Wang, Li; Zhao, Yicheng; Yan, Ming (Frontiers in Microbiology, 2023)
Antimicrobial resistance (AMR) is a global, multifaceted crisis that poses significant challenges to the successful eradication of devastating pathogens, particularly methicillin-resistant Staphylococcus aureus (MRSA), a persistent superbug that causes devastating infections. The scarcity of new antibacterial drugs is obvious, and antivirulence strategies that reduce the pathogenicity of bacteria by weakening their virulence have become the subject of intense investigation. Alpha-hemolysin (Hla), a cytolytic pore-forming toxin, has a pivotal role in S. aureus pathogenesis. Here, we demonstrated echinatin that a natural compound isolated from licorice, can effectively inhibit the hemolytic activity of MRSA at 32 μg/mL. In addition, it did not interfere with bacterial growth and had no significant cytotoxicity at the inhibitory concentration of S. aureus hemolysis. The heptamer formation tightly correlated with Hla-mediated cell invasion, whereas echinatin does not affect deoxycholic acid-induced oligomers of Hla. Echinatin affects hemolytic activity through indirect binding to Hla which was confirmed by the neutralization assay and CETSA assay. Furthermore, RT-qPCR and western blot analysis revealed that echinatin suppressed Hla expression at both the mRNA and protein levels, as well as the transcript levels of Agr quorum sensing system-related genes. Additionally, when echinatin was added to a co-culture system of A549 cells and S. aureus, it significantly reduced cell damage. Importantly, echinatin exhibited a significant therapeutic effect in an MRSA-induced mouse pneumonia model. In conclusion, echinatin significantly inhibited the hemolysin effect and may be a potential candidate compound for combating drug-resistant MRSA infections.